2017
DOI: 10.1111/oik.04415
|View full text |Cite
|
Sign up to set email alerts
|

Patch dynamics and temporal dispersal partly shape annual plant communities in ephemeral habitat patches

Abstract: Most organisms in ephemeral habitat patches have resting stages which form a local species pool in response to temporal variations in the patch's availability and suitability. Temporal dispersal from the local species pool may, therefore, be an important process shaping the community assembly, particularly soon after patch creation, and possibly interacting with environmental filtering. As the temporal variation of the environmental conditions has a major effect on the composition of the local species pool, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 45 publications
2
34
0
1
Order By: Relevance
“…There are typically 25-45 weed species in wheat fields (Henckel et al 2015), although on average four species are found in 1-m 2 quadrats (Bourgeois et al in preparation). In addition, the weed assemblage is influenced by the legacy of past disturbances, depending on the crop history (Mahaut et al 2018), as well as by spatial dispersal between fields (Henckel et al 2015). In addition, the weed assemblage is influenced by the legacy of past disturbances, depending on the crop history (Mahaut et al 2018), as well as by spatial dispersal between fields (Henckel et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There are typically 25-45 weed species in wheat fields (Henckel et al 2015), although on average four species are found in 1-m 2 quadrats (Bourgeois et al in preparation). In addition, the weed assemblage is influenced by the legacy of past disturbances, depending on the crop history (Mahaut et al 2018), as well as by spatial dispersal between fields (Henckel et al 2015). In addition, the weed assemblage is influenced by the legacy of past disturbances, depending on the crop history (Mahaut et al 2018), as well as by spatial dispersal between fields (Henckel et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sufficient dispersal rates are thought to be necessary for species to persist in disturbance prone landscapes (Hanski and 232 Gilpin 1997), but seed banks can maintain local colonization-extinction dynamics in the absence of dispersal from the metacommunity if environmental conditions fluctuate on time scales that 234 are shorter than the range of temporal dispersal by propagules in the seed bank (Mergeay et al 2007(Mergeay et al , 2011Ventura et al 2014). The spatial variation in community dynamics generated by 236 temporal dispersal could appear indistinguishable from that generated by spatial dispersal, but it would be due to purely local processes or as a result of combined spatial and temporal dispersal 238 (Mahaut et al 2018).…”
Section: Community Dynamicsmentioning
confidence: 99%
“…Reestablishment from the seed bank may fail due to niche preemption by similar species that have already emerged from the 242 seed bank, introducing historical contingencies that may have stochastic elements (Fukami 2015;Schwentner and Richter 2015). Species could also emerge from the seed bank under unfavorable 244 environmental conditions (e.g., due to stochastic reactivation or bet hedging), maintaining sink populations in the community via temporal dispersal (a temporal mass effect, Shmida and Ellner 246 1984;Rajaniemi et al 2006;Mahaut et al 2018). Other species might miss favorable opportunities for growth due to misinterpreted environmental cues or failures during the 248 temporal dispersal process (i.e., they are 'dormancy limited') (Donohue et al 2010), which may allow competitively inferior species to occupy habitats that superior competitors fail to 250 recolonize.…”
Section: Community Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations